Fish myxosporeans from the Okavango Delta, Botswana and the south coast of South Africa - Reed, Cecile Catharine (University of the Free State, 2003)
Myxozoans form a diverse and economically important group of endoparasites that have been intriguing researchers ever since the early1800's. These parasites are notorious, having been associated with the devastating effects many species have shown in aquaculture and fisheries industries throughout the world. Research on both freshwater and marine myxosporeans in Africa is limited to a few countries and has, until recently, been largely neglected in southern Africa. In recognition of the need to investigate the presence of fi sh-infecting myxosporeans in both the freshwater and marine environments of southern Africa, a study was initiated in 1997 investigating the biodiversity of myxosporeans infecting fi shes in two very unique southern African localities. Firstly, the Okavango River and Delta in Botswana contains one of the worlds largest inland deltas composed of about 18 000 km2 waterways. Situated in the middle of the Kalahari Desert, this pristine wetland is the only one of its kind that forms an inland delta and one of the few river systems in the world that is visible from space. The research on myxosporeans infecting marine fi shes was conducted along the Cape south coast of South Africa, which has one of the most diverse marine fauna and flora compositions in the world of which 13 % is endemic. This study aimed to review all existing literature concerning freshwater and marine fish-infecting myxosporeans in Africa, report on the biodiversity and prevalence of fi sh-infecting myxosporeans in the Okavango River and Delta, Botswana, investigate the pathogenic potential of myxosporeans infecting the Okavango fi shes, determine the taxonomic status, species biodiversity and prevalence of myxosporeans infecting fi shes along the Cape south coast, South Africa and investigate the pathogenic potential of myxosporeans infecting intertidal and surf zone fi shes along the Cape south coast of South Afri ca. The examination of 285 8 fi shes representing 14 families and 65 species on several field trips to the Okavango Ri ver and Delta from 1997 to 2001 revealed the presence of 29 different fish infecting myxosporeans representing the genera Henneguya Thelohan, 1892 and Myxobolus Btitschli, 1882. Six of these species have been described as new in three articles prior to this study. Another two new species have been recorded in this thesis, together with the records of 14 miscellaneous species that have never been described before, but require more materi al for the completion of species descriptions. During the course of nine surveys conducted along the Cape south coast of South Africa since March 1998, a total of 410 fishes representing 33 species were examined for parasitic infections. Results from these surveys revealed the presence of 15 different myxosporean species. Three species from the genus Ceratomyxa Thelohan, 1892, one species from the genus Henneguya, two from the genus Myxidium Biltschli, 1882, one species from the genus Myxobolus and one species from the genus Sphaeromyxa Thelohan, 1892 are described in this thesis. Two keys for the identification of both the freshwater, as well as marine and estuarine fish-infecting myxosporeans in Africa are presented as a conclusion to this study. The results obtained from this study have laid the foundation for the continuation of research on these parasites in southern Africa and has provided an insight into the great diversity of myxosporeans infecting southern African fishes.

Verteenwoordiges van die Myxozoa vorm 'n diverse en ekonomies belangrike groep endoparasiete wat al sedert die vroee 1800s navorsers betower. Hierdie parasiete word met die vernietigende effekte geassosieer wat hulle in die akwakultuur en vissery-industriee wereldwyd veroorsaak. Navorsing op albei die varswater en mariene miksosporidia in Afrika is tot 'n paar lande beperk en het, tot onlangs, omtrent geensins ' n bestaan in suidelike Afrika gehad nie. Na aanleiding van die tekort aan inligting in verband met varswater en mariene miksosporidia in suidelike Afrika, is 'n projek in 1997 begin om die biodiversiteit van varswater en mariene miksosporidia in twee baie unieke lokaliteite in suidelike Afrika te ondersoek. Eerstens, die Okavangorivier en -delta in Botswana huives een van die wereld se grootse binnelandse deltas wat uit omtrent 18 000 km2 se vloedvlaktes bestaan. Hierdie ongerepte vleiland is in die middel van die Kalahariwoestyn gelee en is een van die enigste riviere ter wereld wat van die buite ruim besigtig kan word. Navorsing op die mariene miksosporidia is teen die Kaapse suidkus van Suid-Afrika gedoen, wat een van die mees diverse en spesieryke fauna en flora ter wereld het en waarvan 13% endemies is. Hierdie studie beoog om alle bestaande literatuur m verband met beide varswater en mariene miksosporidia in Afrika te hersien, te rapporteer op die biodiversiteit en infeksievlakke van visinfekterende miksosporidia in the Okavangrivier en -delta, om die taksonomiese status, spesiediversitiet en voorkoms van miksosporidia in visse van die Kaapse suidkus te ondersoek en om die patogeniese potentiaal van hierdie miksosporidia te bepaal. 'n Totaal van 2858 visse van 14 families en 65 spesies is op verskeie navorsingsopnames vir parasiete ondersoek. Die resultate het die teenwoordigheid van 29 verskillende miksosporia van die genera Henneguya Thelohan, 1892 en Myxobolus Btitschli, 1882 gelewer. Ses van hierdie spesies is vooraf in artikels beskryf. 'n Verdere twee word in hierdie proefskrif beskryf, saam met 'n lys van onbekende spesies wat addisionele inligting benodig vir hul spesiebeskrywings. Gedurende nege opnames aan die Kaapse suidkus van Suid-Afrika sedert Maart, 1998, is 'n totaal van 41 0 visse van 33 spesies vir miksosporidia infeksies ondersoek. Resultate lewer die teenwoordigheid van 15 verskill ende miksosporidia spesies op. Drie spesies van die genus Ceratomyxa Thelohan, 1892, een spesie van die genus Henneguya, twee spesies van die genus Myxidium Btitschli, 1882 en een spesie van die genus Myxobolus word in hierdie proefskrif beskryf. Twee sleutels vir die identifikasie van beide die varswater en mariene miksosporidia in Afrika word as 'n afsluiting tot die proefskrif voorgestel. Die resultate van hierdie studie het die fondasies vir die voortgesette navorsing op hierdie parasiete in suidelike Afrika neergele en het insig tot die ongelooflike diversiteit van miksosporidia in suidelike Afrika gelewer.
Thesis (Ph.D. (Zoology and Entomology))--University of the Free State, 2003
Keywords: Botswana; Cape south coast; Ceratomyxa; Freshwater; Fishes; Henneguya; Marine; Myxidium; Myxobolus; Sphaeromyxa; Myxosporea -- Africa, Southern; Fishes -- Parasites; Fishes -- Diseases; Parasitology -- Africa, Southern